Child and space within the discourse of pedagogy - Klasnić, Irena (Rethinking childhood II: child and space, 2026)
The notion of space has multiple meanings—it can refer to total dimensional relationships and directions, a part of an area, three-dimensional real space with Euclidean geometry, or the material world as a whole. From the pedagogical perspective, space plays an important role in a child’s life. Therefore, it is not surprising that space is considered the third educator—not only in the framework of the Reggio pedagogy, where the concept originated, but also in a broader sense. In the kindergarten and school context, space includes the interior and exterior architecture, as well as the human factor. In any institution, space is a specific micro-universe—one made up of all peculiarities of the stakeholders in the educational process. Within it, various influences interact, establishing multiple forms of interdependences of children/pupils, kindergarten teachers/teachers, parents, and other adults important for children’s growth. Nowadays, children are brought up in different types of space, which requires an individual approach to each child. The quality of space has been changing significantly and at a fast pace; private space is becoming public, and real space is being replaced by virtual space. In the contemporary pedagogical research, the sacrificing of space is becoming a frequently analysed and critically examined phenomenon—children are replacing the outdoor play space with the indoor space; parents lack space for quality time with their children; and peer play is being replaced by cyberspace. In order to increase the positive and reduce the negative influence on children, space must be designed in line with pedagogical guidelines. Such space should be safe, inclusive, encouraging, and directed towards positive values. Furthermore, it should encourage children’s activity, exploration, and creativity. This presentation is grounded in the pedagogical understanding of multidimensional space, with special emphasis on the challenges faced by kindergarten teachers, school teachers, and parents in using space effectively to ensure the holistic development of children.